Design of an Efficient Trustful-Lightweight Cloud Service Provisioning Model using Service Optimizer - Pawar, Suvarna S.; Prasanth, Y. (EAI Endorsed Transactions on Cloud Systems, 2021)
INTRODUCTION: The establishment of trusted cloud services pretends to provide high impactful service with better satisfaction to the web-users and cloud service providers. Moreover, various existing trust-aware algorithms use diverse QoS measurements and related attributes, leading to the complex selection of cloud services. OBJECTIVES: Thus, this research intends to propose a Trustful-Lightweight Cloud Service Provisioning algorithm (TL-CSP) using Service Optimizer (SO). METHODS: Initially, the QoS metrics are determined by evaluating attributes based on a ranking method based on the users’ requests. It is performed with the computation of weighted coefficients of received requests from the users. The service optimization is performed using a global optimizer to assist the cloud users in selecting the service with better satisfaction. RESULTS: The proposed TL-CSP accuracy is validated and compared with the existing cloud service provisioning algorithm to measure the proposed model’s efficiency. CONCLUSION: The simulation is carried out in a MATLAB environment. The proposed TL-CSP intends to shows a better trade-off in contrast to prevailing approaches.